Upaya Balai Pemasyarakatan dalam Menghadapi Hambatan Klien Pemasyarakatan yang Hilang pada Saat Pembimbingan - Addelia Aizah Rachma; Eka Nanda Ravizki (CV Rewang Rencang, 2025)
BAPAS plays a role in guiding, assisting, and supervising the implementation of guidance so that social reintegration runs optimally. BAPAS guidance is carried out on a certain schedule so that correctional clients can be active in society and only carry out their obligations including mandatory reporting only on certain days, this certainly raises the opportunity for clients to be lost during guidance. The method in this study is empirical juridical through interviews with a socio-legal, statutory, and conceptual approach. The results of the study showed that missing correctional clients were searched for through coordination with the police. There needs to be an effort by BAPAS to prevent the loss of clients during guidance through the provision of disciplinary sanctions, verification of information during home visits, and coordination with the local community.